A study on the effect of diabetes and obesity on some lipids and some biochemical parameters of women in AL-Khoums city (Journal of Medical Sciences, 2024)
Obesity and type 2 diabetes mellitus (T2DM) in women are increasing in prevalence owing to decreases in physical activity levels and a shift to diets that include addictive and/or high-calorie foods. These changes are associated with the adoption of modern lifestyles and the presence of an obesogenic environment, which have resulted in alterations to metabolism, adaptive immunity and endocrine regulation. This study clarifies the problem of the large prevalence of Type 2 Diabetes Mellitus (T2DM) with obesity on women in the city of AL-Khoums city and its impact on many chemical parameters.     Many studies have confirmed the impact of diabetes and obesity on women, and thus the possibility of side effects increases if the patient neglects important advice from the doctor or neglects to take periodic treatment. It is difficult to limit the spread of the disease, but it is our duty, along with the scientific seminars and advice provided by the Diabetes Center in AL-Khuoms city, to delay the disease, and to give women all the important information about the dangers. of obesity on public health and the exacerbation of the risk with (T2DM). This study concluded that women with diabetes with obesity showed a significant effect on some lipids such as cholesterol and triglycerides, in addition to its effect on calcium, ferritin and vitamin D, and therefore other complications on body functions are certain.